2018
DOI: 10.1007/s00401-018-1851-x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid neurogranin concentration in neurodegeneration: relation to clinical phenotypes and neuropathology

Abstract: Neurogranin (Ng) is a post-synaptic protein that previously has been shown to be a biomarker for synaptic function when measured in cerebrospinal fluid (CSF). The CSF concentration of Ng is increased in Alzheimer’s disease dementia (ADD), and even in the pre-dementia stage. In this prospective study, we used an enzyme-linked immunosorbent assay that quantifies Ng in CSF to test the performance of Ng as a marker of synaptic function. In 915 patients, CSF Ng was evaluated across several different neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
118
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 56 publications
22
118
2
Order By: Relevance
“…In conclusion, our data shows that Ng is much more closely associated with plaque load compared to the spreading of Aβ pathology. This is in line with previous findings that CSF Ng is positively correlated with CERAD scores in autopsy-confirmed cases of AD [45]. Evaluating the levels of Ng in CSF from patients with primary tauopathies, without amyloid plaque pathology, might give us further insight into the association with tau as previous studies on CSF Ng have shown strong correlations with CSF tau [17, 24, 30, 33, 38, 61].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In conclusion, our data shows that Ng is much more closely associated with plaque load compared to the spreading of Aβ pathology. This is in line with previous findings that CSF Ng is positively correlated with CERAD scores in autopsy-confirmed cases of AD [45]. Evaluating the levels of Ng in CSF from patients with primary tauopathies, without amyloid plaque pathology, might give us further insight into the association with tau as previous studies on CSF Ng have shown strong correlations with CSF tau [17, 24, 30, 33, 38, 61].…”
Section: Discussionsupporting
confidence: 91%
“…We previously showed a strong association between CSF Ng and degree of AD neuropathology independent of diagnosis in a study containing several neurodegenerative diseases [45]. In the present study, we confirmed the CSF study as brain Ng levels were increasing with both Braak stage, CERAD score and to some extent Thal phase, meaning that Ng is associated with both Aβ and tau pathology.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…CSF Ng levels have been extensively investigated in Alzheimer's disease (AD), where they are increased compared to controls, increased in amyloid‐beta (Aβ) + mild cognitive impairment (MCI), and linked to cognitive decline and progression from MCI to AD dementia . A recent postmortem, human brain proteome study on patiens with and without dementia found that synaptic proteins, but not any individual protein, could differentiate PD with dementia (PDD) and dementia with Lewy bodies (DLB) from controls and AD and that cognitive impairment and decline in life correlated with loss of synaptic proteins …”
mentioning
confidence: 99%
“…Few studies have examined CSF Ng in PD, finding unchanged or decreased levels of Ng compared to controls . Even scarcer are studies on Ng and cognitive decline or motor dysfunction, and results are conflicting .…”
mentioning
confidence: 99%